Optimization of urban land-use structure in China's rapidly developing regions with eco-environmental constraints. (April 2019) - Luo, Xiang; Lu, Xinhai; Jin, Gui; Wan, Qing; Zhou, Min
Abstract: Economic growth and eco-environmental protection are largely incompatible in the optimization of the urban land-use structure (ULUS) in rapidly developing regions. Here, we attempted to construct a model for optimizing ULUS with the inclusion of uncertain interval values, simultaneously considering the economic growth and eco-environmental protection in rapidly developing regions so as to estimate the elastic interval value of ULUS. The corresponding urban economic and environmental benefits were analyzed. Furthermore, an empirical study of Wuhan city revealed that there are certain counterbalance relationships among commercial land, industrial land and green land: the area of residential land, green land and public land is increasing year by year, and that of industrial land remains basically unchanged, while that of commercial land is decreasing gradually. Therefore, in rapidly developing regions, greater economic benefits from the ULUS are usually obtained at the cost of environmental and ecological benefits. Highlights: This paper is to optimize the ULUS by using interval uncertainty method, considering the eco-environmental constraints. An uncertain interval linear optimization model was developed with the aim to simulate the ULUS of Wuhan city. Greater economic benefits from the ULUS are usually obtained at the cost of environmental and ecological benefits.